2008
DOI: 10.2147/ndt.s2484
|View full text |Cite
|
Sign up to set email alerts
|

Very early onset and greater vulnerability in schizophrenia: A clinical and neuroimaging study

Abstract: Abstract:Although schizophrenia has been diagnosed in children, this group of disorders has received too little attention in the clinical and research literature. Preliminary data suggest that early onset schizophrenia (EOS) and very early onset schizophrenia (VEOS) tend to have a worse outcome than adult onset schizophrenia, and seem to be related to a greater familial vulnerability, due to genetic, psychosocial, and environmental factors. Recently, advanced neuroimaging techniques have revealed structural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The proportion of patients with EOS is only around 4% of all schizophrenia patients [1]. Those with EOS show an insidious onset, more severe premorbid neurodevelopmental abnormalities, more frequent terrifying visual hallucinations, constant blunted affects, a higher rate of familial psychopathology, minor response to treatment, poorer outcome [2] and more severe cognitive performance [3,4] compared with adult-onset schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of patients with EOS is only around 4% of all schizophrenia patients [1]. Those with EOS show an insidious onset, more severe premorbid neurodevelopmental abnormalities, more frequent terrifying visual hallucinations, constant blunted affects, a higher rate of familial psychopathology, minor response to treatment, poorer outcome [2] and more severe cognitive performance [3,4] compared with adult-onset schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Familial studies have indicated that parents of youth with EOS have higher rates of schizophrenia spectrum disorders than parents of patients with adult-onset illness and relatives of children and adolescents with ADHD (Margari et al, 2008;Nicolson et al, 2003). The risk of developing schizophrenia is about ten times higher if a first-degree relative has the illness.…”
Section: Geneticsmentioning
confidence: 99%
“…Yet, family involvement and intervention become particularly critical when treating a child with EOS as they most likely reside with their family and are dependent upon them to support and access treatment (Asarnow et al, 2004). Familyfocused interventions require an understanding of this system, particularly since familial studies have indicated that parents of individuals with EOS have higher rates of schizophrenia and schizophrenia spectrum disorders than parents of patients with adult-onset illness, and relatives of children and adolescents with ADHD (Margari et al, 2008;Nicolson et al, 2003). Parents of youth with EOS also experience higher levels of social isolation, introversion, suspiciousness, and hostility than parents of children with autism and ADHD (Nicolson et al, 2003).…”
Section: Family Interventionsmentioning
confidence: 99%
“…Additionally, clinical group differences in the N100 repetition suppression response were considered separately in subsamples of participants between 5 and 12 years and 13 and 17 years of age to explore whether very early presentation of CHR or PS is accompanied by more marked plasticity deficits. Research suggests that very early onset psychosis (i.e., emerging before the age of 13 years) shows more severe premorbid neurodevelopmental abnormalities and poorer treatment response and outcomes than later onset psychosis [ 46 48 ]. We hypothesized a progression in plasticity dysfunction from HC to CHR to PS groups.…”
Section: Introductionmentioning
confidence: 99%